Ethiopia–Somaliland Diplomatic Relations Since 1994: Status, Opportunities, and Challenges - Elmi, Abdillahi (Technium Social Sciences Journal, 2026)
This paper is intended to observe the diplomatic relationship between Ethiopia and Somaliland since 1994: status, opportunities, and challenges. The study found that the relationship between Ethiopia and Somaliland exists within a political context expounded by Ethiopia's de jure statehood and Somaliland's de facto status. Additionally, Ethiopia was the first country to allow Somaliland to open a mission office in Addis Ababa in 1994, and it also established the General Consulate in Hargeisa in 2002. Currently, Hargeisa is home to several mission offices, including those from Turkey, the UAE, Britain, and other countries. The study identified Ethio-Somaliland opportunities to increase trade between the two sides and to create an investment exchange. For instance, this presents a significant opportunity for both sides because Somaliland has an 856 km coastline, while Ethiopia is a large and densely populated landlocked country. This situation allows Ethiopia to diversify its port options in neighboring countries to meet its demand, and it also represents a major economic opportunity for the expansion of Berbera port, which has received $442 million in foreign direct investment (FDI) from Emirates Dubai Port World (DP World). The study also highlights that there is future opportunity and hope related to the Grand Ethiopian Renaissance Dam (GERD) because Somaliland is hopeful that as soon as this dam becomes finished, it will acquire cheap and non-environmental-hazard electricity utilities. Ethiopia’s vision also includes selling electricity to Somaliland when the dam is completed so as to earn foreign currency. The study also touches on the fact that since the Horn of Africa region is unstable, the challenges surrounding Ethiopia and Somaliland include terrorism, extremism, human trafficking, informal trade, and illegal immigrants. Similar to other parts of the world, both sides are always alert to the risks their countries face, as is the region's relationship with hardliner terrorist groups. Additionally, although there is a trade imbalance and a deficit on the Somaliland side, both sides indicated that the expansion of Berbera port is complete; Ethiopia will use it more for its export and import goods than it currently does, which will help to balance the trade between the two countries.